Exploring experiences of Western Cape based Shine volunteers about the Shine Centre programme and the children they support - Mashek, Carrie (Department of Social Development, 2015)
The main research questions focused on understanding why people volunteer; their views on the Shine training and Literacy Hour programmes and recommendations that would result in children receiving a high quality education. The findings of the study emphasised the crucial role that volunteers play in the Shine Centre organisation and within the South African education system. These volunteers are a dynamic and diverse group who offer their time for a variety of reasons but are committed to enhancing the literacy rates of primary-aged school children in the Western Cape. Experiences of these community members ranged from gaining skills and techniques from Shine training to working and understanding children with very different backgrounds to themselves. The findings found that there is a high level of satisfaction amongst volunteers with respect to the training and the Literacy Hour sessions. However, there are certain obstacles that volunteers face and which impact on their facilitation of the programme, such as not having the right materials to teach with or a child’s home circumstances, some of which can be very difficult to overcome.